Uso de la dinámica de sistemas para optimizar las rutas de recojo de Residuos Sólidos en el distrito de TARAPOTO - Ramírez Shupingahua, Segundo Roger (2014)
This thesis, "USE OF SYSTEM DYNAMICS TO OPTIMIZE ROUTES OF SOLID WASTE PICK UP IN THE DISTRICT TARAPOTO "; general objective, optimize routes pick ups solid waste in the district of Tarapoto using dynamics systems. Also specific objectives; know the behavior of I gather system solid waste using system dynamics; use system dynamics to model the system solution I gather of solid waste; mathematical models to simulate understand and discuss the results; determining improving routes with Use programming. For the development of the proposed system dynamics was used as methodology, this methodology consists of three phases; conceptualization, presentation or formulation, analysis and evaluation; I obtained in these phases used to predict the behavior of solid waste. From the results obtained in the investigation shows that with the use of system dynamics as a methodology helps to improve the plan collection of solid waste in the district of Tarapoto and programming Linear option is proposed to optimize pick routes Waste Solid district.